2014
DOI: 10.1371/journal.pgen.1004643
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Bacterial Receptor for Lysozyme: Binding of Lysozyme to the Anti-σ Factor RsiV Controls Activation of the ECF σ Factor σV

Abstract: σ factors endow RNA polymerase with promoter specificity in bacteria. Extra-Cytoplasmic Function (ECF) σ factors represent the largest and most diverse family of σ factors. Most ECF σ factors must be activated in response to an external signal. One mechanism of activation is the stepwise proteolytic destruction of an anti-σ factor via Regulated Intramembrane Proteolysis (RIP). In most cases, the site-1 protease required to initiate the RIP process directly senses the signal. Here we report a new mechanism in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 83 publications
8
84
0
Order By: Relevance
“…Moreover, V is necessary for lysozyme resistance in C. difficile (21). In fact, the C. difficile V anti-sigma factor RsiV binds lysozyme and may serve as a direct lysozyme receptor, as it does in B. subtilis (22). An ortholog of X has not been identified in any sequenced C. difficile isolate, but C. difficile strains encode an additional ECF sigma factor, T (csfT or sigT).…”
mentioning
confidence: 99%
“…Moreover, V is necessary for lysozyme resistance in C. difficile (21). In fact, the C. difficile V anti-sigma factor RsiV binds lysozyme and may serve as a direct lysozyme receptor, as it does in B. subtilis (22). An ortholog of X has not been identified in any sequenced C. difficile isolate, but C. difficile strains encode an additional ECF sigma factor, T (csfT or sigT).…”
mentioning
confidence: 99%
“…Under environmental conditions that elevate ECF s factor activity, many integral membrane anti-s factors undergo RIP, as is the case for anti-s factors regulating s E from E. coli and s W and s V from B. subtilis (Chaba et al, 2007;Grigorova et al, 2004;Hastie et al, 2014;Ho & Ellermeier, 2012). RIP is initiated by a highly specific site-1-protease (S1P).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that PrsW, the site-1 protease, is the sensor of the environmental stressor (Ellermeier & Losick, 2006), but further research into the mechanism suggests the involvement of a negative regulator of proteolysis in sensing the stress signal (Heinrich et al, 2009). More recently, the regulation of s V by its anti-s factor RsiV has been investigated (Hastie et al, 2013(Hastie et al, , 2014). Like the s W stress response, the s V stress response chemically remodels cell envelope structure providing resistance to its inducer, lysozyme (Guariglia-Oropeza & Helmann, 2011;Ho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysozyme directly binds to RsiV and induces the cleavage of its C-terminal extracytoplasmic portion by signal peptidase (site-1 cleavage). Subsequently the N-terminal portion is processed by the intramembrane protease RasP (site-2 cleavage), and σ V is released [6] [7].…”
Section: Introductionmentioning
confidence: 99%